SPEECH ACT EXPRESSIONS IN THE ADVERTISEMENTS ON TELEVISION: A Case Study of Three Advertisements Both Food & Health Products and Cell-Phone Provider - Puspita Halim (Jurnal Bahasa Inggris Terapan, 2016)
The study entitled “Speech Act Expressions in the Advertisements on Television: A Case Study of Three Advertisements Both Food & Health Products and Cell-phone Provider” seeks to illuminate the types of speech acts based on Searle (1979) and the approaches of advertisements proposed by Book and Schick (1996). This study mainly uses a qualitative method to analyze the collected data in this research. The data sources are in the form of verbal texts, namely, statements of the speaker’s dialogue and narration both Food & Health Product and cell-phone provider advertisements. These advertisements were taken from several private TV stations aired during 1st March – 30th April 2010. The three advertisements were selected and categorized into four styles, namely, dramatizations, demonstrations, presentations, and testimonials. These commercials were classified into three tones, namely, factual, emotional, and humorous. Furthermore, the research was conducted to investigate the types of speech acts expressed in these different styles and tones of advertisements, namely representatives, directives, commissives, expressive, and declaratives. The study has discovered three tones within testimonial, demonstration, and presentation styles.  Furthermore, it has exposed one emotional tone within presentation style.  And two factual tones within testimonial and demonstration styles. This research has obtained linguistic notion and comprehension for students who are engaged in learning speech act expression in several utterances, mainly advertisements. Keywords: speech act, advertisement, style, tone